The ALTITUTE Project (Institut Nacional d'Educació Física de Catalunya (INEFC), 2011)
In swimming, Olympic medals are often won by fractions of a second. One strategy that is often employed to obtain that advantage is altitude training. Over the past decade, a large amount of altitude training research has led to a new paradigm—the"living high-training low" model. In this approach, athletes live at altitude to gain the advantages of altitude acclimatization, but train at sea level to maximize hard training. Indeed a recent summary of many studies concluded that the potential performance benefit from altitude training for elite athletes could be as high as 1.6% (the difference between a gold medal, and not even making it to the Olympic Games!). However virtually all these studies have been done in land-based athletes with remarkably few studies performed in swimmers. Nevertheless, many sports teams expend precious resources going to altitude without knowing whether they are using the right approach, or even whether they should bother at all. The key question we need to answer is whether altitude training really works for swimmers, as well as why, how, when, and for whom it works.